Research on digital governance based on Web of Science—a bibliometric analysis - Zhao Lin; Mohd Rizal Yaakop (Frontiers in Political Science, 2024)
Exploring digital governance is essential for grasping how technology can be employed to enhance public services, boost efficiency, and foster transparency and engagement. This study aims to conduct a systematic review of digital governance research in order to explore its development, emerging research trends, network of leading researchers, countries and institutions that contribute greatly to this field. A bibliometric study was conducted on digital governance works using the following terms: “digital governance,” “E-governance,” “digital government,” and “E-government” as the keywords. VOSviewer and CiteSpace were two tools used for the bibliometric analysis. Results showed that the United States played a dominate role in digital governance studies, followed by China, the United Kingdom, India, and Spain. Brunel University, University at Albany, and University of Johannesburg were the top three research institutes for digital governance. Reddick C.G., Weerakkody V., Dwivedi, Y. K., Mensah, I. K., and Jaeger, P.T. served as the representative researchers in this field. In addition, topics including usability and reliability of digital governance system, quality assurance under the framework of digital governance, the quality of digital service, impact of digital governance on public perception, effects of digital transformation on public value perceptions were the focal points in recent years.